Ablation of steel under surface irradiation by high-intensity tandem pulses. (January 2018) - Kononenko, V.V.; Konov, V.I.
Abstract: Specific features of interaction of high-intensity (10 15 W cm –2 ) femtosecond laser pulses with ablated vapour are experimentally studied under a tandem (double pulse) regime of irradiation with a short (Δ t = 1 – 11 ns) delay between the pulses. Using interference and shadow photography at a time scale of below 10 ns, data on dynamics of vapour expansion are obtained and the electron density in vapour is estimated. Reasons for observed strong screening of the radiation of the second pulse in a tandem are discussed.